2001
DOI: 10.1177/172460080101600207
|View full text |Cite
|
Sign up to set email alerts
|

Serum Levels of Interleukin-18 and sICAM-1 in Patients Affected by Breast Cancer: Preliminary Considerations

Abstract: Interleukin-18 (IL-18), a cytokine that plays an important role in the T-cell-helper type 1 response, acts as an angiogenesis and tumor suppressor. Intercellular adhesion molecule-1 (ICAM-1) has a potential role in immunoregulation by mediating immune cell infiltration into the tissue. The aim of this study was to evaluate IL-18 and soluble (s) ICAM-1 serum levels in breast cancer (BCa) patients with liver (BCaM1 h) or bone (BCaM1 b) metastases compared to BCa patients without metastases (BCaM0) and healthy do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
25
0
2

Year Published

2002
2002
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(29 citation statements)
references
References 14 publications
2
25
0
2
Order By: Relevance
“…21 Nonetheless, IL-18 is increased in the circulation of patients with different types of cancer. [22][23][24][25][26] Intriguingly, in an experimental tumor model, IL-18 mediated tumor progression through the enhancement of cancer cells' adhesive properties to the vascular endothelium or through proangiogenic activity. 27 Thus, the role of IL-18 in tumor biology and therapy remains a controversial issue.…”
mentioning
confidence: 99%
“…21 Nonetheless, IL-18 is increased in the circulation of patients with different types of cancer. [22][23][24][25][26] Intriguingly, in an experimental tumor model, IL-18 mediated tumor progression through the enhancement of cancer cells' adhesive properties to the vascular endothelium or through proangiogenic activity. 27 Thus, the role of IL-18 in tumor biology and therapy remains a controversial issue.…”
mentioning
confidence: 99%
“…3 Here we report elevated serum levels of bioactive IL-18 in patients afflicted with pancreatic carcinoma. In fact, elevated serum levels of IL-18 have been observed in other tumors including colon carcinoma, 55 lung cancer, 55 hematological malignancies, including myeloma, 56,57 breast cancer, 58,59 gastric carcinoma, 60 esophageal carcinoma, 61 bladder cancer, 62 renal cell carcinoma 63 and head and neck carcinoma. 64 Generally, IL-18 production has been linked to aggressive tumor development and shorter survival times.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the anti-cancer effect of IL-18, its pro-cancerous effect has been recently suggested in gastric cancer patients, the analysis of the expression pattern of IL-18 and tumor progression revealed that IL-18 was expressed highly in the tumor region in comparison with non-tumor region and related with distant metastasis (Ye et al, 2007). Eissa et al (2005) and Merendino et al (2001) have reported that IL-18 is also an important marker of breast cancer progression because higher IL-18 levels were detected in serum from breast cancer patients with metastasis compared to healthy volunteers and breast cancer patients without metastasis.…”
Section: Discussionmentioning
confidence: 99%